PENINGKATAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN MODEL PROBLEM BASED LEARNING SISWA KELAS VIII SMP NEGERI 31 HALMAHERA SELATAN - Faujan Faujan; Darlisa Muhamad (Universitas Khairun, 2022)
This research was conducted with the objectives of (1) to find out how the studentsâ€™ ability in writing explanatory texts was using a problem based laerning model for eighth grade students of SMP Negeri 31 Halmahera Selatan. (2) To find out how to improve the writing of explanatory texts by using problem based learning model for Class VIII students of SMP Negeri 31 Halmahera Selatan. The population and this study were all eighth grade students of SMP Negeri 31 Halmahera Selatan. The sample consisted of 25 students, using quanititative descriptive methods. Based on the results of the analysis and conclusions (1) the resulst of observations, the teacher has conditioned students to participate in the learning process of writing explanatory texts using a problem based laerning model, the teacher has preparedlearning tools and prepared learning package books as learning resources to make it easier for students to find related information. With the material provided. (2) Interviews, explanatory text writing material have been taught to class VIII SMP Negeri 31 South Halamahera using a problem based learning model because the material is contained in the indonesian Languge Education curiculum. (3) The us of the problem Based Learning model can improve the ability tio write explanatory texts. Before this research was conducted, studentsâ€™ writing skills. During that time the learning Â process tend to watch and is boring so that it affects the interest and motivation of students in learning. (4), the success of using the Problem Based Learning model can also be seen in the improvement of the quality of the learning process for writing explanatory texts. It can be seen from the everage score of the explanatory text writing test on the final test of 85,2 which has increased quite well. In addition to the increase in student everage, there was also an increase in the scores for each aspect of the explanatory text, namely (1) title/tipic, 5 (2) content, 4,44,, (3) organization (general statements, esplanations, and interpretations) 4,88, (4) vocabulary, 4,16 and (5) Mechanical, 3,64.